The Role of Compensation and Job Satisfaction to Improve Employee Performance PT. A - Sari Dewi Oktari; Agatha Rinta Suhardi; Andi Budiawan (GoAcademica Research & Publishing, 2023)
The low performance of employees is thought to occur due to less optimal compensation and low job satisfaction felt by employees. This study aims to examine and analyze the effect of compensation and job satisfaction on employee performance at PT. A. Research methods using descriptive and verification, data collection techniques using primary data obtained through questionnaires. The research sample was 82 respondents, the sampling method used purposive sampling. The data analysis technique uses multiple linear regression. The results showed that descriptively compensation, job satisfaction, and employee performance were classified as lacking. As for the verification results obtained that compensation and job satisfaction affect employee performance both partially and simultaneously, with a contribution of 39.9% and the remaining 60.1% influenced by other factors not examined in this study.